Evaluation of plantain (Musaxparadisica) varieties under subtropics of north India - Kumar, Ram; Rajan, S; Singh, Achal (The Indian Journal of Agricultural Sciences, 2005)
Ten plantain (Musa x paradisiaca L.) varieties were evaluated at the experimental farm of the Institute, Lucknow to find out the suitable varieties for commercial cultivation. The highest pseudostem girth was recorded in ’Burdi Chinia’ followed by ’Bhos’,’Chinia’,’Kothia’ and ’Bersain’. The pseudostem height was maximum in ’Chinia’ and ’Bhos’ and minimum in ’Dakhnisagar’ and ’No 15. ’Bhos’ and ’Gauria’ took maximum days (456 days) for a crop cycle and .Dakhnisagar’ (375) and .Chinia’ (383) minimum days. Bunch weight and estimated yieid/ha were maximum in ’Chakkel’, followed by ’Bersain’, ’Bhos’, ’Chinia’, ’Gauria’ and ’Kothia’. Minimum bunch weight, estimated yield/ ha and hand weight were recorded in Dakhnisagar. Finger length was maximum (20.9 cm) in ’Beula’. The finger diameter (5.6 mm ) and weight (218.7g) were higher in ’Bhos’ than the other varieties. On the basis of bunch weight/plant, estimated yield/ha and short crop cycle, varieties ’Chakkei’, ’Chinia’, ’Bersain’, ’Kothia’, respectively, were found suitable for commercial cultivation in subtropics of north India.